Analisis Penerapan Markerless Augmented Reality pada Video Game Memancing dengan Pendekatan Simultaneous Localization and Mapping (SLAM) - Dany Muhammad; Wibisono Sukmo Wardhono; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In the development of application that utilize augmented reality, one of the most common approach is using a special marker. However, a marker can limit the player's freedom when playing a video game that utilize augmented reality. This research will develop an augmented reality video game without any marker (markerless) using Simultaneous Localization and Mapping (SLAM) approach. SLAM is an approach of constructing or updating a map of a certain environment while keeping track of an agent's location at the same time. SLAM is implemented in an augmented reality fishing game which use marker so that the game can be played without any marker. The markerless function will be implemented using VOID AR package in Unity game engine. After markerless function implemented, black box testing is used to observe if virtual object can appear correctly in the environment. The testing result shows that markerless augmented reality fishing game can be developed with SLAM method using VOID AR package in Unity. The virtual object looks most stable when the environment that recorded in frame is not changed much. This is happened because it is easier for video game application to use SLAM approach when the features are not changed much. When the camera is directed to the new environment, new features are recorded, make it harder for video game application to adapt.